Tunnel Overbreak Management System Using Overbreak Resistance Factor - Jang, Hyong Doo (KOREAN SOCIETY FOR ROCK MECHANICS AND ROCK ENGINEERING, 2020)
When tunnel is excavated via drilling and blasting, the excessive overbreak is the primary cause of personal or equipment safety hazards and increasing the cost of the tunnel operation owing to additional ground supports such as shotcrete. The practical management of overbreak is extremely difficult due to the complex causative mechanism of it. The study examines the relationship between rock mass characteristics (unsupported face condition, uniaxial compressive strength, face weathering and alteration, discontinuities- frequency, condition and angle between discontinuities and tunnel contour) and the depth of overbreak through using feed-forward artificial neuron networks. Then, Overbreak Resistance Factor (ORF) has been developed based on the weights of rock mass parameters to the overbreak phenomenon. Also, a new concept of tunnel overbreak management system using ORF has been suggested.